2021
DOI: 10.1007/s10658-020-02190-8
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome characterization of strains belonging to the Ralstonia solanacearum species complex and in silico analysis of TaqMan assays for detection in this heterogenous species complex

Abstract: Identification and classification of members of the Ralstonia solanacearum species complex (RSSC) is challenging due to the heterogeneity of this complex. Whole genome sequence data of 225 strains were used to classify strains based on average nucleotide identity (ANI) and multilocus sequence analysis (MLSA). Based on the ANI score (>95%), 191 out of 192(99.5%) RSSC strains could be grouped into the three species R. solanacearum, R. pseudosolanacearum, and R. syzygii, and into the four phylotypes within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…However, as the number of sequenced genomes increases, some published primers might be found to be less specific. A recent in silico analysis based on 192 RSSC genomes indicated that false positive or false negative results were possible in previous PCR assays because of a lack of sufficient sequencing information to guarantee primer specificity and coverage ( 49 ). Similarly, a study of Pseudomonas aeruginosa revealed that a previously developed method based on restricted numbers of sequences could only detect 82.1% of tested strains, and the novel assay designed using 1,000 genomes of P. aeruginosa and 1,017 genomes of other pathogens could detect all tested strains ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, as the number of sequenced genomes increases, some published primers might be found to be less specific. A recent in silico analysis based on 192 RSSC genomes indicated that false positive or false negative results were possible in previous PCR assays because of a lack of sufficient sequencing information to guarantee primer specificity and coverage ( 49 ). Similarly, a study of Pseudomonas aeruginosa revealed that a previously developed method based on restricted numbers of sequences could only detect 82.1% of tested strains, and the novel assay designed using 1,000 genomes of P. aeruginosa and 1,017 genomes of other pathogens could detect all tested strains ( 50 ).…”
Section: Discussionmentioning
confidence: 99%